A new genus of grasshoppers (Orthoptera: Acrididae: Spathosterninae) from Thailand - Dawwrueng, Pattarawich; Storozhenko, Sergey Yu.; Vitheepradit, Akekawat (Zootaxa, 2025)
A new genus of Spathosterninae, Tenasserimacris gen. nov. (type species: T. punctata sp. nov.), was discovered and described from a lower montane forest in Tenasserim Mountain Range of western Thailand, Khao Krajom in Ratchaburi Province. Clearly, this genus is similar to Beybienkoacris Storozhenko in the presence of parallel veinlets on the radial area of tegmina. However, this new genus differs from the latter in the temporal foveolae in both sexes, shape of ventral genicular lobe of hind femur in female, shape of furculae on 10th abdominal tergite in male, shape of valves of cingulum and apical valves of penis, shape of epiphallus, and shape of female subgenital plate. Additionally, tribe Tristrini is transferred from subfamily Tropidopolinae to Spathosterninae. Lastly, the composition and distribution of subfamily Spathosterninae are briefly discussed.